Dynamics of infections with gastrointestinal parasites and Dictyocaulus viviparus in dairy and beef cattle from Costa Rica - Maranda, L. (2007)
A longitudinal survey was carried out to determine and describe the prevalence and intensity of gastrointestinal parasite infections and Dictyocaulus viviparus in a dairy and a beef cattle farm of two different ecological zones in Costa Rica. The influence of anthelmintic treatment, age and meteorological factors (rainfall, minimum and maximum temperatures) on gastrointestinal nematodes and D. viviparus counts was determined. Calves were subjected to monthly sampling of feces and blood between April 2002 and March 2003. Coprological techniques were used to detect gastrointestinal helminthes, protozoan and D. viviparus. Blood samples were analyzed for antibodies to D. viviparus by ELISA. The most prevalent gastrointestinal parasites detected on both farms (dairy cattle, A; beef cattle, B) were Eimeria spp. (94.7%, 93.7%), Strongylidae (75.0%, 81.4%), Buxtonella sulcata (38.0%, 21.6%) and Strongyloides papillosus (29.8%, 31.7%), whereas Moniezia benedeni (4.8%, 9.1%), Trichuris spp. (7.3%, 13.2%), Toxocara vitulorum (0.0%, 1.8%) and Entamoeba bovis (2.5%, 1.1%) were less prevalent. Mean fecal egg counts (FEC) showed highest values of Strongylidae in April, May and July (>335.3 eggs/g feces) on farm A, and April, May and August (>304.3 eggs/g feces) on farm B. S. papillosus presented low FEC throughout the year on farm A, on farm B the highest values were obtained in April (303.0 eggs/g feces). Trichuris spp. presented maximum FEC values in May (328.6 eggs/g feces) on farm A and in June (157.5 eggs/g feces) on farm B. Treatment and age had significant influence on infection intensity of Strongylidae (farms A and B), S. papillosus (farms A and B) and Trichuris spp. (farm A). Rainfall had significant effect on S. papillosus (farms A and B) and Trichuris spp. (farm B). Maximum temperature showed significant effect on S. papillosus (farm A) and Trichuris spp. (farms A and B). Minimum temperature had significant influence on Strongylidae (farm A), S. papillosus (farms A and B) and Trichuris spp. (farm B). Haemonchus spp. (57%, 66%) and Cooperia spp. (30.0%, 30.7%) were the most prevalent genera identified by coproculture on both farms, in contrast, Trichostrongylus spp. and Oesophagostomum spp. were less frequent. Patent lungworm infections were low on both farms (10.8%, 1.8%). On farm A, high prevalence of antibodies against D. viviparus was determined only at the beginning of the study, in contrast, on farm B the seroprevalence fluctuated throughout the year. Treatment, age and maximum temperature had significant effect on D. viviparus counts on farm A, but not on farm B.